Обоснование чисел подобия и масштабов физического моделирования процесса формирования центральной пористости в непрерывнолитой заготовке (Modern Problems of Metallurgy, 2020)
The article describes the preparatory stage of the experiment on the study of regularities in the formation of central porosity in the volume of continuous cast billets. Based on the basic principles of the similarity theory and the experience accumulated in this subject, the authors proposed similarity numbers and calculated scales to simulate the processes of solidification of the billet that take place at the final stages of solidification, which lead to the formation of an internal defect – central porosity.